The increase of physiological optimum of nitrogen for plants by inoculation and use of plant growth regulators - Volkogon, V.V. (Сільськогосподарська мікробіологія, 2008)
As was established in greenhouse experiments ssusing isotope dilution method and confirmed by field investigations, conducted on grey-forest and sod-podzol soils, the inoculation and (or) treatment of cereal grasses with growth stimulators enhances plants’ physiological optimum in nitrogen and thus improves ecological state of agrocenoses by increasing fertilizers assimilation rate and their involvement into the constructive metabolism. At this, typically high doses of mineral nitrogen combined with plants growth stimulators become ecologically acceptable. У вегетаційних дослідах за використання методу ізотопного розбавлення та у польових, проведених на сірому лісовому та дерново-підзолистому ґрунтах, показано, що інокуляція та (або) обробка злакових трав стимуляторами росту сприяє зростанню фізіологічного оптимуму азоту для рослин, і внаслідок цього – поліпшенню екологічної обстановки в агроценозах через зростання ступеню засвоєння добрив і залучення їх до конструктивного метаболізму. При цьому високі за типових умов дози мінерального азоту, застосовані у поєднанні з бактеріальними препаратами або стимуляторами росту рослин, переходять у розряд екологічно доцільних. В условиях вегетационных опытов при использовании метода изотопного разбавления и в полевых, проведенных на серой лесной и дерново-подзолистой почвах, показано, что инокуляция и (или) обработка злаковых трав стимуляторами роста способствует увеличению физиологического оптимума азота для растений, и вследствие этого – улучшению экологической обстановки в агроценозах при увеличении степени усвоения удобрений и вовлечения их в конструктивный метаболизм. При этом высокие в типичных условиях дозы минерального азота, примененные в сочетании с бактериальными препаратами или стимуляторами роста растений, переходят в разряд экологически приемлемых.